Civil liability for oil pollution damage caused by ships: Chinese legal system and reference to Vietnam - Pham Van Tan (Cogent Business & Management, 2019)
Along with the development of the maritime industry, the Vietnam's Sea is facing marine pollution caused by oil discharge from ships. The cases of insufficient and unsatisfactory compensation for pollution damage caused by ship's oil are increasing. Therefore, this paper focused on the analysis of the status and the weakness of Vietnam legal system on civil liability for oil pollution damage caused by ships. In order to find out solutions for such improvement of the legal system, this paper focuses on the systematic analysis of the Chinese laws of civil liability for oil pollution damage caused by ships. Through such analysis, the paper gives some lessons for Vietnam learned from the experience of China in the implementation of laws of civil liability for oil pollution damage caused by ships.
Keywords: 650; civil liability; ships’ oil pollution; compensation for oil pollution damage